New Muslim Generations: Shaping Self-Image, Reshaping Religion: A Theoretical and Empirical Study of Inter-Religiosity with Muslim Youth in the Alps-Adriatic Region - Donlic, Jasmin (Religions, 2023)
This paper focuses on the everyday religious practices of second-generation Muslims who have been born, raised, and socialized in the Alps-Adriatic region. These individuals are developing their own forms of religiousness and perspectives on religion. Religious practices are often regarded as a mere continuation of Islamic traditions in the countries from which their parent generation migrated. However, this generation practices religion in ways that are shaped by socialization in a largely secularized postmodern society and by inter-religiosity, i.e., interaction between people with different beliefs that provokes them to reflect on attitudes, altering their perspectives. Whereas their parents or grandparents more or less lived in their own bubble, mainly because they did not speak the language well enough, the new generation see inter-religious interaction and communication as a matter of course—part of the everyday practices that they take for granted. The empirical section of this paper looks at the experiences and everyday practices of the new Muslim generation. It draws on a participatory project focusing on the photovoice method, which involved Muslim youth not as the subjects of research but as co-researchers. In addition to this approach, the methodology incorporated phenomenological anecdotal research and reading. Adopting a participatory approach, the young people reported on their specific everyday experiences and everyday inter-religious practices. In the process, they described not only their experiences of foreignness and exclusion but also transcultural strategies and ways to address such experiences, such as adopting a self-confident position, taking action, and developing hybrid life plans.